Mixed Adenoneuroendocrine Tumor of the Rectum in an Ulcerative Colitis Patient - Gaspar,Rui (2019)
Patients with inflammatory bowel disease present a higher risk of colorectal cancer, especially patients with a high degree of disease activity. Although rare, carcinoid tumors can also be associated with inflammatory bowel disease. Mixed adenoneuroendocrine tumor is defined as a neoplasm with dual differentiation (neuroendocrine and adenoma) with each component accounting for at least 30% of the tumor. We present a case of a mixed adenoneuroendocrine tumor in a patient with inflammatory bowel disease.